Aberrant gene-specific DNA methylation signature analysis in cervical cancer. Issue 3 (March 2017) - Bhat, Samatha; Kabekkodu, Shama Prasada; Varghese, Vinay Koshy; Chakrabarty, Sanjiban; Mallya, Sandeep P; Rotti, Harish; Pandey, Deeksha; Kushtagi, Pralhad; Satyamoorthy, Kapaettu
Multicomponent molecular modifications such as DNA methylation may offer sensitive and specific cervical intraepithelial neoplasia and cervical cancer biomarkers. In this study, we tested cervical tissues at various stages of tumor progression for 5-methylcytosine and 5-hydroxymethylcytosine levels and also DNA promoter methylation profile of a panel of genes for its diagnostic potential. In total, 5-methylcytosine, 5-hydroxymethylcytosine, and promoter methylation of 33 genes were evaluated by reversed-phase high-performance liquid chromatography, enzyme-linked immunosorbent assay based technique, and bisulfate-based next generation sequencing. The 5-methylcytosine and 5-hydroxymethylcytosine contents were significantly reduced in squamous cell carcinoma and receiver operating characteristic curve analysis showed a significant difference in (1) 5-methylcytosine between normal and squamous cell carcinoma tissues (area under the curve = 0.946) and (2) 5-hydroxymethylcytosine levels among normal, squamous intraepithelial lesions and squamous cell carcinoma. Analyses of our next generation sequencing results and data from five independent published studies consisting of 191 normal, 10 low-grade squamous intraepithelial lesions, 21 high-grade squamous intraepithelial lesions, and 335 malignant tissues identified a panel of nine genes ( ARHGAP6, DAPK1, HAND2, NKX2-2, NNAT, PCDH10, PROX1, PITX2, and RAB6C ) which could effectively discriminate among the various groups with sensitivity and specificity of 80%–100% (p < 0.05). Furthermore, 12 gene promoters (ARHGAP6, HAND2, LHX9, HEY2, NKX2-2, PCDH10, PITX2, PROX1, TBX3, IKBKG, RAB6C, and DAPK1) were also methylated in one or more of the cervical cancer cell lines tested. The global and gene-specific methylation of the panel of genes identified in our study may serve as useful biomarkers for the early detection and clinical management of cervical cancer.